Psychological Research using Linguistic Inquiry and Word Count (LIWC) and Korean Linguistic Inquiry and Word Count - 이창환; 김경일; 임종섭; 이윤형 (Journal of cognitive science, 2015)
Language analysis methodologies such as LIWC and KLIWC, its Korean version, have been used widely in psychology and other social sciences. Given this context, this review aims to overview previous psychological findings based on the language analysis methodologies and compare findings deriving from LWIC and KLIWC. More specifically, this review examines important results in clinical psychology, developmental psychology, personality psychology, cognitive psychology, and other social sciences. Further, this review evaluates major debates regarding the language analysis methodologies and provides a possible future direction for using the methodologies in the cognitive science field. KCI Citation Count: 0